Implemetation of Religious Moderation in the Ministry of Religion South Sulawesi Province - Muhammad Syuja’i; Mukhtar Alshodiq (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2025)
The rapid flow of information through social media influences the implementation of religious moderation in society, particularly in the office environment. The phenomenon of moderation through social media platforms has become a space for the emergence of various religious issues, which influence each person's perspective on religious matters. The purpose of this paper is to determine the implementation of religious moderation in the office environment, specifically within the Ministry of Religious Affairs in the South Sulawesi province. The method used is descriptive qualitative, with sources gleaned from literature that correlates with the problem. Data collection comes from journals, ebooks, websites, and YouTube. The results and discussion of this paper are: Implementing religious moderation is not enough to be done individually, but must be done systematically and institutionally, even by the state. The state must be present to facilitate the creation of a healthy public space, so that communication between people of different religions and beliefs can be fostered. Providing all facilities and not restricting them is a just and wise moderate attitude. Having a moderate nature for all ASN employees will realize the benefits of religious life and harmony, peace, and tolerance within the nation.